Low cycle fatigue life of the alloy IN718 enhanced through surface nanostructuring - Kumar, Sanjeev; Chattopadhyay, K.; Singh, Vakil; Satyanarayana, D.V.V.; Kumar, Vikas (Elsevier Inc., 2020)
Surface nanostructure was developed on the peak aged IN718 superalloy using surface mechanical attrition treatment (SMAT) and its influence was studied on low cycle fatigue (LCF) behaviour. The gauge section of LCF samples was SMATed with steel balls of 3 mm for the duration of 5 min at constant frequency of 20 kHz using StressVoyager to modify the surface. Surface grains of 36 μm were refined to ~49 to 73 nm following SMAT. Strain controlled cyclic tests were performed for the non-SMATed and SMATed samples at ±Δεt/2 from ±0.50% to ±1.0% at strain rate (ė) 1 × 10−3 s−1 under reversed loading (R = –1) at room temperature. LCF life of the SMATed specimen at Δεt/2 = ±0.50%, was enhanced by more than twice that of the non-SMATed specimen.
Keywords: IN718 alloy; LCF life; Nanostructure; Surface mechanical attrition treatment